Steven D. Levitt and Stephen J. Dubner. Superfreakonomics: Global Cooling, Patriotic Prostitutes, and Why Suicide Bombers Should Buy Life Insurance. London: Penguin Books Ltd. 2009. 270 pages. Paperback. £ 14.99. (The Pakistan Development Review, 2009)
Behavioural economics is an emerging field and superfreakonomics provides useful insights into human behaviour observed with respect to issues that have economic implications. The underlying theme of the book is that human beings respond to incentives. The authors have set up a number of interesting examples to convey how different incentives work. The case studies discussed in the book are based on the authors’ recent academic research; motivated by fellow economists as well as engineers and astrophysicists, psychotic killers and emergency room doctors, amateur historians and transgender neuroscientists. Most of the stories fall into one of the two categories: things you always thought you knew but in fact did not; and things you never knew you wanted to know, but do know. The authors, with the help of data, show that drunk walking is eight times more dangerous than drunk driving. The message is that the misaligned incentives (penalties) are responsible for this—only drunk driving is penalised. To show the influence of positive incentives the authors demonstrate how cable TV might have improved the status of women in India. A baby Indian girl, who does grow into adulthood, faces discrimination in provision of education, health care and remuneration in job market. In a national health survey, 51 per cent of Indian men said that wife-beating is defensible under certain situations and more surprisingly, 54 per cent of the women agreed. But things are changing, albeit at a slow pace. The authors find that cable TV has empowered Indian rural women—families with cable TV are more likely to have a lower birth rate and more schooling.